2013
DOI: 10.1016/j.ijcard.2012.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Heart involvement in Rheumatoid Arthritis: Systematic review and meta-analysis

Abstract: Our systematic review pointed out the strength and the grade of both pericardial and cardiac valvular involvement in RA patients. Our findings underscore the importance of an echocardiographic assessment at least in clinical research when RA patients are involved. Moreover, further research is needed to understand the possible relationship of our findings and the increased cardiovascular mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 24 publications
2
48
0
5
Order By: Relevance
“…To date, three systematic reviews and meta-analyses are available as cornerstones regarding cardiac alterations in RA patients [4,5,20,21]. The data of our previous meta-analysis highlights that RA patients without confounding comorbidities have first, a significant valvular, aortic root and pericardial involvement.…”
Section: Discussionmentioning
confidence: 87%
“…To date, three systematic reviews and meta-analyses are available as cornerstones regarding cardiac alterations in RA patients [4,5,20,21]. The data of our previous meta-analysis highlights that RA patients without confounding comorbidities have first, a significant valvular, aortic root and pericardial involvement.…”
Section: Discussionmentioning
confidence: 87%
“…Valvular involvement in RA may be more prevalent than previously thought [45]. Wisklowska et al found valvular abnormalities in 47 % using TTE, while Roldan et al reported a prevalence of 59 % using transoesophageal echocardiography (TEE) [6,7].…”
Section: Valve Diseasementioning
confidence: 97%
“…1). A recent meta-analysis showed a 10-fold increase in valvular nodules in patients with RA compared with controls [45]. The nodules are single or multiple, oval lesions, 4 to 12 mm in size with regular borders, homogenous echocardiographic reflectance and no calcification.…”
Section: Valve Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…En la literatura se describe la asociación de PMR y derrame pleuropericárdico en raras ocasiones 9-13 , como comentan los autores, en tanto que la asociación entre EORA -tanto seronegativa como seropositiva-con la presencia de derrame pleural o pericárdico está ampliamente descrita 14,15 .…”
Section: Sr Editorunclassified